STUDENTS’ PERCEPTION ABOUT THE EFFECT OF SCHOOL LIBRARY IN THEIR READING COMPREHENSION ACHIEVMENT - Riano E Mokalu; Meity Muntuuntu; Jim R Tuna (KOMPETENSI, 2021)
The aims of this research was to find out whether or not, the Students’ Perception about School Library a Affects their Reading Comprehension Achievment. This research was conducted at SMA NEGERI 1 LANGOWAN. The subjects were 30 students’ of XI grade, which consisted of 25 sample. The instrument for data collection was taken from student’s questionnaire based on Likert scale. The results showed that Since Pearson r (1.00) is bigger than r(table) (0.361) at p. 0.05 and df 28, it can then be stated that the null hypothesis (ho) is rejected, and alternative hypothesis (ha) is accepted at p 0.05 and df 28. This, in other words, means that students’perception about school library in affecting their reading comprehension are positively correlated. Thus, in turn, students who are predicted to have high reading comprehension,according to the researcher that the influence of the school library is very high to develop students' reading comprehension. In this case the researcher considers that the relationship between the school library and students’ is very important.That means there was a positive correlation between students’ perception about school library and their reading comprehension achievment.